PELATIHAN PEMBUATAN SURAT LAMARAN PEKERJAAN (APPLICATION LETTER) DAN RIWAYAT HIDUP (CURRICULUM VITAE) BAGI SISWA SMKN 07 BATAM - Nurma Dhona Handayani; Lenny Husna; Afriana Afriana (PUAN INDONESIA, 2026)
Training on writing job application letters and Curriculum Vitae (CV) for Vocational High School (SMK) students aims to prepare students with essential competencies required when entering the workforce. Although SMK students are equipped with practical and technical skills in specific fields, many of them lack adequate skills in preparing professional job application documents. The ability to write an effective job application letter and a well-structured CV is a crucial complementary skill that can significantly improve graduates’ employment opportunities after completing their studies.The objective of this training is to provide SMK students with practical skills in writing professional job application letters and CVs, to help them understand how to tailor these documents to specific job positions and target companies, and to enhance their self-confidence in facing the recruitment and selection process. The training methods consisted of theoretical explanations combined with hands-on practice, group discussions to share experiences and strategies in preparing job application documents, simulations of job application letter and CV writing, direct feedback from instructors, and demonstrations on developing attractive CVs that comply with industry standards. The benefits of this training include improved students’ ability to prepare professional job application documents, increased confidence in applying for jobs, better understanding of how to highlight skills and experiences effectively, and enhanced awareness of the importance of written communication as an essential competency for young professionals. This training is expected to better prepare SMK students for entering the workforce and succeeding in the recruitment process.